The Impact of Organizational Learning on Business Continuity Through the Moderating Effect of Organizational Culture: A Study of UAE’s Public Sector Organizations - Loubna Saad Saoud (2025)
Despite the UAE’s vast growth, its public sector remains essential to its stability, where effective crisis management and fast change are unique challenges. It is crucial to understand the relationship between organizational learning (OL), business continuity (BC), and organizational culture (OC). This paper examines the OL and BC relationship through the moderating role of OC, specifically the hierarchical culture that is applied in the UAE's public sector. The study aims to expand OL and BC literature. Empirical data was collected using the questionnaire method. The study hypothesized that OL has a positive impact on BC and that OC moderates the relationship between OL and BC. The study findings indicate that the OL process has a direct and positive impact on BC in the context of the UAE public sector. However, the study reveal that the OC does not moderate the relationship between OL and BC, which sheds light on the complexity of this relationship and can guide future research. Thus, the study findings have the potential to assist UAE public sector organizations in developing their OL activities, fostering an OC, and enhancing effective strategies for BC.